INTERVENSI SOSIAL DALAM SOSIALISASI SEXUAL HARASSMENT - Aprillia Salnabila Jasmine; Jasmine, Arsalan Ayri Fath, Elicia Yolanda Putri, Zahra Khairunnisa, Zaky Eka Hermita, Rijal Abdilla (ADISAM PUBLISHER, 2025)
This study explores the pressing issue of sexual harassment in Indonesia, with an emphasis on increasing awareness among university students through a psychoeducational intervention. The primary objective of the study was to educate students about the characteristics of sexual harassment and empower them with information on what steps to take if they become victims. The intervention included distributing informative posters and conducting sessions where respondents shared personal stories to foster empathy and understanding among peers. The sampling method focused on university students on campus, despite the constraints of their busy schedules, which made it difficult to collect respondents. Findings suggest that the psychoeducational approach was able to increase awareness and understanding of sexual harassment, with respondents expressing a greater willingness to support peers who may have been affected. Overall, this study highlights the importance of educational initiatives in combating sexual harassment and promoting a safer campus environment for all students